Towards Smart Tech 4.0 in the Built Environment Applications of Disruptive Digital Technologies in Smart Cities, Construction, and Real Estate - Ullah, Fahim (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint captures recent advancements in the introduction, usage, and adoption of smart and digital disruptive technologies in the built environment. It consists of 17 chapters covering a range of topics and article types. The key topics include the adoption of smart technologies, automation, and disruption in the built environment, such as wearable devices and augmented reality in construction safety, electronic process monitoring for construction tasks, digital capture of buildings through point clouds, UAVs, and LIDAR, BIM for a learning environment, underground works and wood construction, collaborative information management technologies in construction, techniques for structural health monitoring and evaluation, construction risk management, inclusive walking communities, smart spin models for cities, landfill and waste management in cities, and circular economy in construction for sustainable development.